An ω-3, but Not an ω-6 Polyunsaturated Fatty Acid Decreases Membrane Dipole Potential and Stimulates Endo-Lysosomal Escape of Penetratin - Zakany, Florina; Szabo, Mate; Batta, Gyula; Kárpáti, Levente; Mándity, István M.; Fülöp, Péter; Varga, Zoltan; Panyi, Gyorgy; Nagy, Peter; Kovacs, Tamas (Frontiers in Cell and Developmental Biology, 2021)
Although the largely positive intramembrane dipole potential (DP) may substantially influence the function of transmembrane proteins, its investigation is deeply hampered by the lack of measurement techniques suitable for high-throughput examination of living cells. Here, we describe a novel emission ratiometric flow cytometry method based on F66, a 3-hydroxiflavon derivative, and demonstrate that 6-ketocholestanol, cholesterol and 7-dehydrocholesterol, saturated stearic acid (SA) and ω-6 γ-linolenic acid (GLA) increase, while ω-3 α-linolenic acid (ALA) decreases the DP. These changes do not correlate with alterations in cell viability or membrane fluidity. Pretreatment with ALA counteracts, while SA or GLA enhances cholesterol-induced DP elevations. Furthermore, ALA (but not SA or GLA) increases endo-lysosomal escape of penetratin, a cell-penetrating peptide. In summary, we have developed a novel method to measure DP in large quantities of individual living cells and propose ALA as a physiological DP lowering agent facilitating cytoplasmic entry of penetratin.